Immunoevasion strategies for African swine fever virus: Modulation of antigen presentation pathways - Penghao Lv; Zhichao Wang; Haowei Chen; Yanru Chen; Hanlin Liao; Kaiyue Wei; Shuying Lv; Min Cui (Virulence)
African swine fever virus (ASFV), a highly lethal pathogen, poses a catastrophic threat to global pork production. While some commercial vaccines exist, their availability remains regional limitations. This review investigates the mechanistic interplay between ASFV and antigen-presenting cells (APCs), with a particular focus on viral evasion strategies that disrupt antigen presentation pathways. Although current understanding of ASFV immunology has largely focused on monocyte/macrophage infection, we provide a systematic analysis of ASFV-mediated immunosuppression across various APCs, including dendritic cells (DCs), B lymphocytes, and γδ T cells, and compare these mechanisms with those employed by other viral pathogens. Key objectives include: (1) synthesizing ASFV-induced dysregulation of antigen presentation, (2) identifying critical gaps in APC-virus interactions, and (3) guiding vaccine development priorities. By highlighting understudied DC-ASFV interplay and potential molecular targets, this work provides a strategic framework for next-generation vaccine design based on host-pathogen conflict at the antigen presentation interface.